A 3-D evaluation of transverse dentoalveolar changes and maxillary first molar root length after rapid or slow maxillary expansion in children - Jacob,Helder Baldi (2019)
ABSTRACT Objective: The objective of the present study was to conduct a randomized clinical trial comparing the effects of rapid maxillary expansion (RME) and slow maxillary expansion (SME). Maxillary permanent first molar root length and tooth movement through the alveolus were studied using cone-beam computed tomography (CBCT). Methods: Subjects with maxillary transverse deficiencies between 7 and 10 years of age were included. Using Haas-type expanders, children were randomly assigned to two groups: RME (19 subjects, mean age of 8.60 years) and SME (13 subjects, mean age of 8.70 years). Results: Buccal cortical, buccal bone thicknesses and dentoalveolar width decreased in both groups. In the RME group the greatest decrease was related to distal bone thickness (1.26 mm), followed by mesial bone thickness (1.09 mm), alveolar width (0.57 mm), and the buccal cortical (0.19 mm). In the SME group the mesial bone thickness decreased the most (0.87 mm) and the buccal cortical decreased the least (0.22 mm). The lingual bone thickness increased in the RME and SME groups (0.56 mm and 0.42 mm, respectively). The mesial root significantly increased in the RME group (0.52 mm) and in the SME group (0.40 mm), possibly due to incomplete root apex formation at T1 (prior to installation of expanders). Conclusions: Maxillary expansion (RME and SME) does not interrupt root formation neither shows first molar apical root resorption in juvenile patients. Although slightly larger in the RME group than SME group, both activation protocols showed similar buccal bone thickness and lingual bone thickness changes, without significant difference; and RME presented similar buccal cortical bone changes to SME.